Dietary modification dampens liver inflammation and fibrosis in obesity‐related fatty liver disease. (10th May 2013) - Larter, Claire Z.; Yeh, Matthew M.; Haigh, W. Geoffrey; Van, Derrick M.; Brooling, John; Heydet, Deborah; Nolan, Christopher J.; Teoh, Narci C.; Farrell, Geoffrey C.
<x xml:space="preserve">Abstract</x> Background: Alms1 mutant (foz/foz) mice develop hyperphagic obesity, diabetes, metabolic syndrome, and fatty liver (steatosis). High‐fat (HF) feeding converts pathology from bland steatosis to nonalcoholic steatohepatitis (NASH) with fibrosis, which leads to cirrhosis in humans. Objective: We sought to establish how dietary composition contributes to NASH pathogenesis. Design and Methods: foz/foz mice were fed HF diet or chow 24 weeks, or switched HF to chow after 12 weeks. Serum ALT, NAFLD activity score (NAS), fibrosis severity, neutrophil, macrophage and apoptosis immunohistochemistry, uncoupling protein (UCP)2, ATP, NF‐κB activation/expression of chemokines/adhesion molecules/fibrogenic pathways were determined. Result: HF intake upregulated liver fatty acid and cholesterol transporter, CD36. Dietary switch expanded adipose tissue and decreased hepatomegaly by lowering triglyceride, cholesterol ester, free cholesterol and diacylglyceride content of liver. There was no change in lipogenesis or fatty acid oxidation pathways; instead, CD36 was suppressed. These diet‐induced changes in hepatic lipids improved NAS, reduced neutrophil infiltration, normalized UCP2 and increased ATP; this facilitated apoptosis with a change in macrophage phenotype favoring M2 cells. Dietary switch also abrogated NF‐κB activation and chemokine/adhesion molecule expression, and arrested fibrosis by dampening stellate cell activation. Conclusion: Reversion to a physiological dietary composition after HF feeding in foz/foz mice alters body weight distribution but not obesity. This attenuates NASH severity and fibrotic progression by suppressing NF‐κB activation and reducing neutrophil and macrophage activation. However, adipose inflammation persists and is associated with continuing apoptosis in the residual fatty liver disease. Taken together, these findings indicate that other measures, such as weight reduction, may be required to fully reverse obesity‐related NASH.